Actual coal mining in north of Peru - Giraldo Paredez, Emiliano (2007)
The present article is the result of the study of 20 mines in addition to not taken others in account in the present analysis, of which 18 are of anthracite, 1 semi bituminous and 1 of graphite; all these mines are located in the mountainous areas of the departments La Libertad, Ancash and Amazonas. The mining of the coal in the north of our country, is being handled mainly by unreliable people, being caused by the coal hoarders, without concerning the forms, methods nor conditions to them under which this substance is extracted. The ruling poverty in the carboniferous zones, has pushed the villagers to venture themselves and to risk in operating the carboniferous deposits, the majority of the cases without any technical manual nor the minimum conditions of safety. Some cases, the holders of the mining concessions, have entered agreement with the proprietary communities of superficial lands, for them make the works of operation, providing to them the materials and necessary tools, a remuneration and until technical consultant’s office in very precise cases, thus to have all the production. One concludes that extremely urgent and necessary the intervention of the state, doing campaign and fomenting consultant’s office to the informal miners to aim who regularize their situation, so that of that form they can sell his products to righter prices, mainly the subsistence of the mines is preserved.